The use of lie detectors (polygraphs) as evidence of expert statements in premeditated murder (Study of Decision Number 796/Pid.B/2022/PN Jkt.Sel) - Cahyo Nugroho (Goodwood Publishing, 2023)
Purpose: This study aims to determine the importance of using a Polygraph in court in proving the premeditated murder case committed by Ferdy Sambo and the judge's considerations in deciding the premeditated murder case based on Law Number 8 of 1981 concerning the Criminal Procedure Code. Research Methodology: This study aims to determine the importance of using a Polygraph in court in proving the premeditated murder case committed by Ferdy Sambo and the judge's considerations in deciding the premeditated murder case based on Law Number 8 of 1981 concerning the Criminal Procedure Code. Results: The Panel of Judges in Ferdy Sambo's trial found the fact that Ferdy Sambo had been convoluted and inconsistent in providing information, so that the Public Prosecutor to strengthen his charges continued the trial with the agenda of hearing witnesses and hearing expert testimony. The results and analysis of the Polygraph examination are written reports included in the evidence in the Indonesian criminal evidence system such as documentary evidence, expert opinions, and guidelines. Willa Wahyuni?12/16/2022 Reading 3 minutes The Polygraph Machine is used at the request of the investigator based on the needs of the investigation of a criminal case.